Pengaruh Literasi Keuangan Teknologi Informasi, Dan Modal Minimal Terhadap Minat Investasi Saham Di Pasar Modal Syariah - Hansen Rusliani; Beid Fitrianova Andriani; Heri Heri (STEKOM PRESS, 2024)
Analyzing influence of financial literacy, information technology, and minimum capital on interest in investing in shares in the Islamic capital market. Financial literacy (X1) has a significant positive effect on investment interest (Y). Tcount value is 4.156 > Ttable 1.662 and the Sig value is 0.000 < 0.05. Information technology (X2) has a significant positive influence on Investment Interest (Y). Calculated T value of the information technology variable is 6.120 > 1.662 with a significance value of 0.000 < 0.05. Minimum capital (X3) has an insignificant positive influence on investment interest (Y). The T value of the minimum capital variable is 2.812 > 1.662 with a significance value of 0.06 > 0.05. Financial literacy, information technology and minimum capital together have a significant effect on investment interest. Significance values ​​(X1), (X2) and (X3) simultaneously influence (Y) by 0.000 < 0.005 and value of Fcount > Ftable (79.354 > 2.700).